The Effect of Project-Based Learning with Gamification and Self-Efficacy on The Software Operation Ability of Junior High School Students - Siti Maysyarah; Citra Kurniawan; Ence Surahman (Journal of General Education and Humanities, 2026)
This study addresses the problem of limited software operation skills among junior high school students and the need for learning strategies that simultaneously enhance technical competence and learner confidence. The objective of this research is to examine the effect of gamification-based Project-Based Learning (PjBL) and students’ self-efficacy levels on software operation skills in Informatics learning. A quasi-experimental method with a posttest-only control group design and a 2×2 factorial arrangement was used, with an experimental group receiving gamified PjBL and a control group receiving non-gamified PjBL. Data were analyzed using two-way ANOVA to identify the effects of learning strategy, self-efficacy, and their interaction on students’ performance. The findings show that students who learned through gamified PjBL demonstrated higher software operation skills than those who experienced PjBL without gamification. The results also reveal a substantial difference in performance between students with high and low self-efficacy, indicating that confidence plays a crucial role in mastering digital technical skills. Although no statistically significant interaction was found between learning strategy and self-efficacy, descriptive analysis suggests that gamification provides greater benefits for students with low self-efficacy by helping reduce skill gaps. Overall, this study confirms that integrating gamification into PjBL effectively improves software operation skills, while reinforcing the importance of strengthening self-efficacy in technology-based learning environments.